2022
DOI: 10.3390/curroncol29110683
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Perioperative Outcomes on Neoadjuvant Hormone Therapy before Laparoscopic and Robot-Assisted Surgery for Localized High-Risk Prostate Cancer in a Chinese Cohort

Abstract: Objective: To analyze the perioperative outcomes of neoadjuvant hormone therapy (NHT) before laparoscopic and robot-assisted surgery for localized high-risk prostate cancer in a Chinese cohort. Methods: The clinical data of 385 patients with localized high-risk prostate cancer who underwent radical prostatectomy (RP) in our hospital from January 2019 to June 2021 were analyzed retrospectively, including 168 patients with preoperative NHT and 217 patients with simple surgery. Clinical characteristics were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…The main finding of our study is that the NHT patients did not experience major complications or readmissions after RARP. Our findings are in line with Naiki et al, who found in their laparoscopic prostatectomy series that the perioperative morbidity of NHT patients was equivalent to that of non-NHT patients [6]. On the contrary, radiotherapists reported hormonal therapy to be associated with higher comorbidities, especially in patients with cardiovascular risk factors [4,5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The main finding of our study is that the NHT patients did not experience major complications or readmissions after RARP. Our findings are in line with Naiki et al, who found in their laparoscopic prostatectomy series that the perioperative morbidity of NHT patients was equivalent to that of non-NHT patients [6]. On the contrary, radiotherapists reported hormonal therapy to be associated with higher comorbidities, especially in patients with cardiovascular risk factors [4,5].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, they were higher in NHT patients (21.8% compared to 5.4% in the NNHT group). This is in contrast to others who noted lower positive surgical margins and a lower PSA recurrence rate in NHT patients [6]. This might be somewhat explained by the trial of nerve-sparing in sexually motivated men harvesting aggressive tumors.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Although several guidelines recommend that surgery be part of a comprehensive treatment for high-risk PCa [ 2 , 4 ], pathological findings suggest that a relatively high proportion of PSM may not be cured by RP and consequently require adjuvant therapy [ 38 ]. Therefore, neoadjuvant therapy is administered to improve surgical and oncologic outcomes in patients with high-risk PCa [ 15 , 16 , 40 , 41 , 42 ]. NHT prior to RP has been tried in combination with cytotoxic agents as it was found to increase the negative surgical margin rate but not prevent BCR [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, three cohort studies showed that NHT prior to RP failed to lead to a significant BRFS advantage compared to RP alone (pooled HR, 1.00; 95% CI, 0.78-1.54) [41]. Sun et al [42] retrospectively analyzed clinical data from 385 patients with high-risk PCa who underwent RP, including 168 patients who underwent neoadjuvant NHT followed by RP and 217 patients who underwent RP alone. Although patients who received neoadjuvant ADT had shorter operative times, decreased volume of blood loss, lower rates of PSM, and higher rates of downstaging GG after RP (p<0.05), there were no statistically significant improvements in BCR, BRFS, or perioperative complications [42].…”
Section: Neoadjuvant Therapy Prior To Rp For High-risk Pcamentioning
confidence: 99%